Rancangan Aplikasi Bergerak Penjadwalan Distribusi Sembako pada UD. Kuning Mas Palangka Raya - Viktor Handrianus Pranatawijaya (Universitas Palangka Raya, 2019)
The role of suppliers and customers greatly affect the distribution of basic food that will be realized in distribution scheduling. In addition to suppliers and customers, several factors used in the preparation of scheduling are the location of suppliers and customers, time / period, and the route of the trip that is formed along with the status of the food delivered. The initial step in making an application is needed is to make an analysis and design first. So the model used in this study is a modified Waterfall model. In the analysis section an application needs search is performed to determine the properties of the application to be made, such as management of user access rights and existing facilities and business process modeling using Unfied Modeling Language (UML), namely use case diagrams, activity diagrams, and class diagram. At the design stage it is used to create software blueprints. The things done include database design and application interface. Existing facilities in this application that must be available are login and registration facilities, managing supplier and customer data as well as couriers, ordering groceries, and scheduling the distribution of groceries, as well as the status of food distribution. For further development of this research can implement the design of applications that are made. Moreover, it can determine the method of finding the route with the shortest distance or the route with the fastest time